Link-Adaptive Distributed Coding for Multisource Cooperation. (10th February 2008) - Cano Cano, Alfonso Alfonso; Wang Wang, Tairan Tairan; Ribeiro Ribeiro, Alejandro Alejandro; Giannakis Giannakis, Georgios B. Georgios B.
Abstract : Combining multisource cooperation and link-adaptive regenerative techniques, a novel protocol is developed capable of achieving diversity order up to the number of cooperating users and large coding gains. The approach relies on a two-phase protocol. In Phase 1, cooperating sources exchange information-bearing blocks, while in Phase 2, they transmit reencoded versions of the original blocks. Different from existing approaches, participation in the second phase does not require correct decoding of Phase 1 packets. This allows relaying of soft information to the destination, thus increasing coding gains while retaining diversity properties. For any reencoding function the diversity order is expressed as a function of the rank properties of the distributed coding strategy employed. This result is analogous to the diversity properties of colocated multi-antenna systems. Particular cases include repetition coding, distributed complex field coding (DCFC), distributed space-time coding, and distributed error-control coding. Rate, diversity, complexity and synchronization issues are elaborated. DCFC emerges as an attractive choice because it offers high-rate, full spatial diversity, and relaxed synchronization requirements. Simulations confirm analytically established assessments.